The Influence of Organizational Culture and Teamwork on Employee Engagement: The Role of Achievement Motivation as Mediation - Delarosa, St. Via; Winarno, Winarno (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The Badan Pertanahan Nasional Klaten served as the research site for this study, which tested and analyzed the relationship between teamwork and organizational culture and employee engagement, using achievement motivation as a mediating factor. Direct questionnaire distribution is the quantitative research approach used. Pegawai Negeri Sipil of the Badan Pertanahan Nasional Klaten served as the study's population. Saturated sampling was employed in this study, and the sample size consisted of 82 civil servants, of whom 56% were men, 40% were between the ages of 50 and 58, and 35% were employed in the Survey and Mapping Section. The period of data gathering in 2023 lasted from September 13 to October 16, 2023. Using the SmartPLS 4 program, the multivariate analysis structural equation model technique was employed for data analysis. The study's findings demonstrated that employee engagement is significantly impacted negatively by organizational culture. Employee Engagement is positively and significantly impacted by teamwork. Employee engagement is positively impacted by organizational culture through the mediation of achievement motivation. Employee engagement is positively impacted by teamwork through the mediation of achievement motivation.